2015
DOI: 10.1007/s10098-015-0986-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emulsion fuel on engine emissions–A review

Abstract: Emulsion fuel is an unconventional fuel for diesel engines, which can be used without modifications in the engine. The benefits of an emulsion fuel include lowering the emissions of nitrogen oxides (NO x ) and particulate matter (PM) which are harmful to health and cause diesel engines to suffer. This paper explains in detail the effect of water in the emulsion fuel on the emissions of NO x , PM, carbon monoxide (CO), hydrocarbon (HC), smoke and exhaust temperature. Experimental results from various researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 98 publications
0
26
0
Order By: Relevance
“…It is believed that FWE has a potential application as an alternative fuel in compression ignition engines [20]. The addition of water to the fuel in the form of FWE leads to the reduction of NOx emissions and the temperature of exhaust gases in this type of drive units [20][21][22][23][24]. However, the review work in the conclusions was inconsistent as to the impact of FWE on CO emissions.…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that FWE has a potential application as an alternative fuel in compression ignition engines [20]. The addition of water to the fuel in the form of FWE leads to the reduction of NOx emissions and the temperature of exhaust gases in this type of drive units [20][21][22][23][24]. However, the review work in the conclusions was inconsistent as to the impact of FWE on CO emissions.…”
Section: Of 15mentioning
confidence: 99%
“…However, the review work in the conclusions was inconsistent as to the impact of FWE on CO emissions. In [20], an increase in CO emissions is indicated as a result of adding water to fuel, while in [21][22][23], it is concluded that the impact of FWE on CO emissions is ambiguous.…”
Section: Of 15mentioning
confidence: 99%
“…Despite these advantages, the diesel engine still gives drawback to human and environment due to emission exhausted from this engine likes Nitrogen Oxides (NOx) and Particulate Matters (PM). PM alone or in combination with other air pollutants can cause respiratory and cardiovascular problems, while NOx and PM can cause acid rain, climate changes, water and soil deterioration in environmental problems [3]. Due to these severe issues, strict regulations such as the Kyoto Protocol was introduced [4] to mitigate these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, emulsion fuels tend to be too expensive and too unstable for practical purposes and have never been widely accepted [3]. For a literature review of emulsion fuels, see reference [4]. However, the benefits from using an emulsion fuel can be significant and this remains an active area for fuel combustion researchers [5,6].…”
Section: Introductionmentioning
confidence: 99%